Clinical measurement of compensatory torsional eye movement during head tilt. Issue 2 (2nd August 2016) - Lim, Han Woong; Kim, Ji Hong; Park, Seung Hun; Oh, Sei Yeul
Abstract: Purpose: To measure the degree of compensatory torsional eye movement during head tilt using a fundus photography method. Methods: We enrolled 55 healthy subjects who were 20–66 years of age. Fundus photographs were obtained in the presumed baseline position and in stepwise head tilt positions to evaluate ocular torsion using a non‐mydriatic fundus camera. Horizontal marks on the nose were photographed simultaneously to evaluate head tilt. Images were analysed using Photoshop to measure the degree of ocular torsion and head tilt. Results: A consistent compensatory torsional eye movement was observed in all subjects during head tilt. The degree of compensatory torsional eye movement showed a positive correlation with the angle of head tilt. Ocular torsional disconjugacy was observed during head tilt, with larger excycloductional eye movement than incycloductional eye movement (4.88 ± 2.91° versus 4.50 ± 2.76°, p < 0.001). In multiple linear regression analysis, the degree of compensatory torsional eye movement was significantly associated with the degree of head tilt ( β = 0.191, p < 0.001), and the direction of cycloduction ( β = −0.548, p < 0.001). Conclusions: The fundus photography method is a non‐invasive, accurate and objective tool for measuring compensatory torsional eye movement. Considering the availability of fundus photography in clinical ophthalmology practice, the proposed method can be used as a clinical tool to measure compensatory torsional eye movement.